Pelatihan Caregiver Lansia dalam Pemberian Pertolongan Pertama pada Fraktur dan Dislokasi - Oda Debora; Maria Prieska Putri Panglipur Ati; Nanik Dwi Astutik (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Nowadays, informal caregiver for elderly are largely needed. Unfortunately, they do not get formal education about health. This causes the services provided to be limited from previous experiences, discussions with friends who have been in similar conditions, or the words of friends. This condition can reduce the quality of caregiver services and the quality of life of the elderly. The provision of education and training for informal caregivers is expected to help overcome this condition. Objective: to improve informal caregiver knowledge and skills about fracture and dislocation. Method: discussion and direct practice method were used. Result: the informal caregivers participation were 100% for all meetings. The comprehension about fracture and dislocation first aid also improved, proven by pre and post test score. Based on observation using check list, the skill were also increased. Conclussion: some researches showed that contiuous education and practice for informal caregiver can reduce stres and improve their ability to served elderly. It was shown form the result that the carever comprehension and skill was also increase. Similar activities can be done in order to establish caregiver better coping mechanism and confdence.